Destroy Experimental Architecture! - Lebbeus Woods (Oz, 1992)
Several years ago, following the Research Institute for Experimental Architecture (RIEA) First Conference on Experimental architecture, I wrote the following statements: Experimental architecture propels architecture as an activity and result into unknown realms, without sanction, justification, or the promise of usefulness to anyone.